2014
DOI: 10.1007/s00066-014-0751-9
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection of targeted and bystander cells by methylproamine

Abstract: IntroductionRadioprotective agents are of interest for application in radiotherapy for cancer and in public health medicine in the context of accidental radiation exposure. Methylproamine is the lead compound of a class of radioprotectors which act as DNA binding anti-oxidants, enabling the repair of transient radiation-induced oxidative DNA lesions. This study tested methylproamine for the radioprotection of both directly targeted and bystander cells.MethodsT98G glioma cells were treated with 15 μM methylproa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Early experiments highlighted the multiple roles of ROS and RNS in bystander effects. Specifically, they showed that radical scavengers (ascorbic acid, N-acetyl l -cysteine), NOS inhibitors (NG-nitro- l -arginine methyl ester [L-NAME]), NO scavenger (2-4-carboxyphenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide [c-PTIO] ( 281 ), antioxidant enzymes (superoxide dismutase [SOD], catalase) ( 10 , 303 ), and DNA-binding antioxidants (methylproamine) ( 39 ) inhibit the appearance of bystander effects. For example, genomic instability due to bystander effects can be rescued by restoring mitochondrial function through overexpression of manganese-dependent superoxide dismutase (MnSOD) ( 103 ).…”
Section: Off-target Effects: An Integrated Cell Response To Radiamentioning
confidence: 99%
“…Early experiments highlighted the multiple roles of ROS and RNS in bystander effects. Specifically, they showed that radical scavengers (ascorbic acid, N-acetyl l -cysteine), NOS inhibitors (NG-nitro- l -arginine methyl ester [L-NAME]), NO scavenger (2-4-carboxyphenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide [c-PTIO] ( 281 ), antioxidant enzymes (superoxide dismutase [SOD], catalase) ( 10 , 303 ), and DNA-binding antioxidants (methylproamine) ( 39 ) inhibit the appearance of bystander effects. For example, genomic instability due to bystander effects can be rescued by restoring mitochondrial function through overexpression of manganese-dependent superoxide dismutase (MnSOD) ( 103 ).…”
Section: Off-target Effects: An Integrated Cell Response To Radiamentioning
confidence: 99%
“…Obviously, the same concepts and possibilities apply to the use of foci assays as pharmacodynamic tools for characterising anti-cancer therapies [Redon et al, 2010a], combinations of therapeutics [Sak et al, 2009] or DNA damage response modifiers, whether used alone or in combination with DNA-damaging treatments [e.g. Lim et al, 2014;Srivastava et al, 2014;Burdak-Rothkamm et al, 2015b]. In cells undergoing apoptosis H2AX phosphorylation occurs in an intranuclear shell.…”
Section: Genotoxicity Testingmentioning
confidence: 99%
“…A delayed DDR is well-established for the cellular RIBE (Sedelnikova et al, 2007). Interestingly, methylproamine protects bystander cells in the in vitro RIBE setting, e.g., if present with recipient cells at the time of transfer of media irradiated cells (Burdak-Rothkamm et al, 2015). By contrast, in the context of targeted radiation effects, methylproamine must be present before and during irradiation to endow radioprotection of cultured cells (Lobachevsky et al, 2011), consistent with the mechanism (DNAbinding antioxidant) of radioprotection (Martin and Anderson, 1998).…”
Section: Development Of Strategies For Prevention Protection and Mitmentioning
confidence: 95%